THE INFLUENCE OF DIGITAL FINANCIAL LITERACY, PERCEPTION OF BENEFITS, AND INTEREST ON STUDENTS’ HABIT IN CARRYING OUT DIGITAL PAYMENT TRANSACTIONS - Hidayani (MSJ : Majority Science Journal, 2023)
This study aims to examine the influence of three exogenous latent variables, namely digital financial literacy, perception of benefits, and interest in one endogenous latent variable, namely student habits in conducting digital payment transactions. the purpose of this study is to determine the influence of digital financial literacy, perceived benefits, and interest in student habits in conducting digital payment transactions with the following hypotheses: H1: Digital financial literacy has a positive effect on students' habits in conducting digital payment transactions.H2: The perception of benefits has a positive effect on students' habits in conducting digital payment transactions. H3: Interest has a positive effect on students' habits in making digital payment transactions.The sample of this study was students of the faculty of economics and business, Mulawarman University with a total of 154 respondents. Data was collected through questionnaires with simple random sampling techniques. The research data were analyzed using SmartPLS 4. The results of this study showed that the perception of benefits and interests had a significant positive effect on student habits, namely P value of 0.000 and 0.044, respectively. Meanwhile, digital financial literacy has a positive insignificant effect on student habits, namely the p value of 0.121.